SECURITY CULTURE AND ITS IMPORTANCE FOR HUMANITY - Saidkhodjaeva Nafisa Saidolimovna (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article defines the concept of security culture. The role of security culture in human society, its three levels and many components are discussed. The main criteria of safety culture for any security object are specified. The main ways and means of promoting and disseminating a culture of security in the country are outlined. In the concluding part, it is necessary to change the consciousness and culture of society by teaching the course "Safety of Life" to solve new pressing problems and challenges of the country in a market economy.